Critical training of mass media documentalists - Garcia-Gutierrez, Antonio; Martinez-Avila, Daniel [UNESP] (Epi, 2014)
This study takes the old myth of objectivity in media discourse to one of the most important but unrecognized actors in the process of its construction: the mass media information scientist or documentalist. Accepting the subjective presence of the documentalist in his/her productions, this article opts for the recognition and explicit statement of this role, recommending two actions. First, we suggest that public higher education institutions combine the technical training of mass media documentalists with training in critical thinking skills. Our study analysed the subjects covered in course syllabi to detect the deficiencies to be addressed in meeting this objective. Second, we propose alternative lines of training that can contribute to cross-training of mass media documentalists in those degree programs to ensure that they acquire the needed skills in critical analysis.
Keywords: Critical analysis; Critical thinking skills; Critical thinking training; Critical thinking education; Documentalists; Information scientists; Press rooms; Mass media; Newspapers; Press; Subjectivity; Objectivity; Ethics; Hermeneutics; Text co-production; Reality construction; Historical memory